Characterization of signaling pathways activated by the interleukin 1 (IL-1) receptor homologue T1/ST2. A role for Jun N-terminal kinase in IL-4 induction - FALLON, PADRAIC; O'NEILL, LUKE ANTHONY JOHN (American Society for Biochemistry and Molecular Biology, 2002)
T1/ST2 is a member of the interleukin (IL)-1 receptor superfamily, possessing three immunoglobulin domains extracellularly and a Toll/IL1R (TIR) domain intracellularly. The ligand for T1/ST2 is not known. T1/ST2 is expressed on Type 2 T helper (Th2) cells, and its role appears to be in the regulation of Th2 cell function. Here, we have investigated T1/ST2 signal transduction, using either transient overexpression of T1/ST2 or a cross-linking monoclonal antibody to activate cells. We demonstrate that T1/ST2 does not activate the transcription factor NF-?B when overexpressed in murine thymoma EL4 cells, or in the mast cell line P815 treated with the anti-T1/ST2 antibody. However, a chimera comprising the extracellular domain of the type 1 IL-1 receptor and the intracellular domain of T1/ST2 activates NF-?B both by overexpression and in response to IL-1. This artificial activation requires the IL1RAcP recruited via the extracellular portion (IL1R1) of the chimera. T1/ST2 is, however, able to activate the transcription factor activator protein-1 (AP-1), increase phosphorylation of c-Jun, and activate the MAP kinases c-Jun N-terminal kinase (JNK), p42/p44 and p38. Anti-T1/ST2 also induces the selective expression of IL-4 but not IFN-? in naive T cells. Importantly, this effect is blocked by prior treatment with the JNK inhibitor SP600125 confirming that JNK as a key effector in T1/ST2 signaling. The lack of effect on NF-?B when T1/ST2 is homodimerized identifies T1/ST2 as the first member of the IL-1 receptor superfamily so far studied that is apparently unable to activate NF-?B, consistent with evidence indicating the lack of a role for NF-?B in Th2 cell function.
PUBLISHED
Keywords: Clinical Medicine